Sarah Coakley, The Broken Body. Israel, Christ and Fragmentation - Schlenker, Christian (Theologische Rundschau, 2025)
Sarah Coakley, The Broken Body. Israel, Christ and Fragmentation. Hoboken (NJ): Wiley Blackwell 2024, 336 S.